IT Implementation in Improving Administration - Muhamad Fathurrohman; Sya'roni Ma'shum (Center for Studies in Advanced Science, 2025)
The implementation of public services based on information technology in SMAN 1 PUNCU to see if the problems that exist in licensing services are better or not using technology equipment. This research was conducted also to look at the benefits and obstacles to the implementation of information technology in public service based on information technology. To look at acomplex problem that requires in-depth understanding, this research method uses descriptive qualitative. For the result of that, it is necessary to do the interview, observation, and documentation study to be able to get valid data. Based on the results of this study concluded that the quality of public services based on information technology has been dissatisfactory. The indicators of public policy implementation are seen through communication, resources, disposition, and bureaucratic structure with the consideration of transparency, participation, and efficiency aspect